Optimalisasi Peran Pola Asuh Orang Tua Terhadap Tumbuh Kembang Balita di PAUD Belimbing Desa Jatiroto Kecamatan Jatiroto Kabupaten Lumajang - Putri Rahayu Ratri; Veronika Vestine; Surya Dewi Puspita; Miftahul Jannah; Sabran Sabran (PEKAT: Jurnal Pengabdian Kepada Masyarakat, 2022)
About 1-3% of children aged 0-5 years in the world experience Developmental delay. Many factors can hinder children's motor development, including nervous disorders, vestibular or balance disorders, and sensory disturbances. Apart from internal factors in the body, children's development is also influenced by environmental (social) factors. The role of parents is crucial in achieving the child's normal growth and development. PAUD Belimbing is a place for early childhood education located in Jatiroto village, Lumajang, East Java. Early childhood development detection activities have never been carried out in PAUD Belimbing. In addition, the understanding of people who know about children's growth and development is still lacking. This service has a strategy of optimizing the role of parents in supporting the success of the maximum growth and development of each child, especially PAUD Belimbing students in Jatiroto village, Lumajang, East Java. The purpose of this optimization activity is expected to increase the knowledge and skills of parents on toddler growth and development. The method used in this service activity includes counselling with IEC media (presentations and giving modules), the practice of child development assessment, discussion, and evaluation. The final result of the evaluation obtained from counselling and practice is an increase in good knowledge of child growth and development. It is expected that parents will be able to apply the knowledge in everyday life and spread this knowledge to friends, relatives, and the surrounding community.